1986
DOI: 10.1128/jb.167.1.191-200.1986
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of mutations in Escherichia coli that selectively influence the growth of hybrid lambda bacteriophages carrying the immunity region of bacteriophage P22

Abstract: Mutations in two Escherichia coli genes, sipA and sipB, result in a specific inhibition of the growth of certain hybrid lambdoid bacteriophages, A immRI2, that have the early regulatory regions and adjacent genes from bacteriophage P22. The sipB391 mutation maps near minute 56 and exerts the strongest inhibitory effect on the growth of the hybrid phages. The sipAl mutation maps near ninute 72 and plays an auxiliary role: enhancing the action of sipB391. Such a role is not limited to sipAl, since there is a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…The clpX::Kan strain was prepared through P1 transduction of W3110 with a P1 lysate of BW25113 ⌬clpX from the Keio collection (4). -P22 hybrid bacteriophages immP22 c2-5 dis and immP22 c1-7 dis have been described previously (46). Plasmid pPW500 (31) encodes -cI-N-trpAt nonstop reporter mRNA regulated by a P TRC promoter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clpX::Kan strain was prepared through P1 transduction of W3110 with a P1 lysate of BW25113 ⌬clpX from the Keio collection (4). -P22 hybrid bacteriophages immP22 c2-5 dis and immP22 c1-7 dis have been described previously (46). Plasmid pPW500 (31) encodes -cI-N-trpAt nonstop reporter mRNA regulated by a P TRC promoter.…”
Section: Methodsmentioning
confidence: 99%
“…SmpB and tmRNA functions are required for lytic development of the immP22 c2-5 dis hybrid phage but not for lytic development of the related immP22 c1-7 dis phage (29,38,46,52). The molecular basis for this strict dependence of immP22 c2-5 dis hybrid phage on SmpB and tmRNA is currently not clear.…”
Section: Transposon Mutagenesis Screenmentioning
confidence: 99%
“…7). Friedman and coworkers found that the sipB phenotype of certain E. coli mutant hosts corresponds to the excision of the CP4-57 cryptic prophage (39,48). The mutant phenotype is failure of a X-P22 dis hybrid phage to grow.…”
Section: Sg20780 Cured Of the Cryptic Prophage) The Four Sg20780mentioning
confidence: 99%
“…We have previously reported the isolation of a variant of E. coli K-12 that, unlike its parent, fails to support growth of certain hybrid phages formed by recombination between E. coli phage X and Salmonella typhimurium phage P22 (38). This E. coli variant, however, supports growth of and most other lambdoid phages.…”
mentioning
confidence: 99%
“…The nonessential immI region, which has no analog in X, encodes the ant (antirepressor) gene and associated regulatory genes (42). The growth of X-P22 hybrids in E. coli with the sipB391 mutation depends on the extent of P22 genetic material substituted for genetic material and on the nature of the sipA allele carried by the bacterium (38). E. coli with the sipB391 mutation and what we have arbitrarily designated the wild-type sipA allele fails to support growth of a X-P22 hybrid carrying the immI-through-immC region of P22 (Fig.…”
mentioning
confidence: 99%